2021
DOI: 10.3390/f12121750
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Biocontrol Potential of Two Ash Endophytes against Hymenoscyphus fraxineus Using In Vitro Plant–Fungus Dual Cultures

Abstract: Development of effective biocontrol procedures using ash endophytes to combat an ash pathogen Hymenoscyphus fraxineus would be an appropriate contribution to the ongoing effort to protect European ash stands against ash decline. In this study we investigated the biocontrol potential of two ash endophytes, Thielavia basicola and Minimidochium sp., against H. fraxineus using in vitro plant-fungus and fungus-fungus dual cultures approach in three biocontrol models. The tests aimed to determine whether the endophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Until now, biological protection measures have primarily focused on the identification and testing of various antagonistic microorganisms, primarily endophytic or saprophytic fungi in the tissues of ash trees ( Fraxinus spp. ), and their potential against H. fraxineus (Bakys et al., 2022; Becker et al., 2020; Bilański & Kowalski, 2022; Haňačková, Havrdová, et al., 2017; Kowalski & Bilański, 2021, 2022; Nawrot‐Chorabik et al., 2021; Schlegel et al., 2016). An antagonism study in planta showed that the practical application of endophytic fungi reduced necrotic lesions on trees (Barta et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, biological protection measures have primarily focused on the identification and testing of various antagonistic microorganisms, primarily endophytic or saprophytic fungi in the tissues of ash trees ( Fraxinus spp. ), and their potential against H. fraxineus (Bakys et al., 2022; Becker et al., 2020; Bilański & Kowalski, 2022; Haňačková, Havrdová, et al., 2017; Kowalski & Bilański, 2021, 2022; Nawrot‐Chorabik et al., 2021; Schlegel et al., 2016). An antagonism study in planta showed that the practical application of endophytic fungi reduced necrotic lesions on trees (Barta et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to cryopreservation, the morphogenetic potential and features of given cell lines are preserved, including the ability to produce specific secondary metabolites [ 8 ]. It is also possible to select genotypes resistant to biotic factors [ 9 , 10 ]. Cryopreservation has also been used to eliminate viruses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These research groups tested their isolates in co-culture with H. fraxineus, identifying multiple inhibitory isolates which could potentially be developed into biocontrol agents. Nawrot-Chorabik et al [7] went one step further in that they also tested two endophytes, Thielavia basicola and Minimidochium sp., in in vitro plant-fungus systems (callus cultures and callus-regenerated seedlings). When these in vitro systems were inoculated with H. fraxineus, they only remained healthy and showed no defense responses when in co-culture with endophytes.…”
Section: Introductionmentioning
confidence: 99%